Crescimento micelial de Ganoderma lucidum em diferentes substratos e relação com concentração de β-Glucanas, atividade antioxidante e efeitos sobre o desempenho de coelhos - Henrique, Katia Atoji (2015)
Ganoderma lucidum is a medicinal mushroom traditionally consumed in Asian countries that presents several beneficial effects already verified. Despite all studies about their bioactive compounds, the best cultivation media enrichment aiming to increase the production of these compounds is still uncertain. Besides, few studies are related to the performance of production animals. In order to test different cultivation media for G. lucidum mycelia, agricultural residues (solid state fermentation) and different sugars and aminoacids (in culture media with agar), were tested to evaluate G. lucidum mycelium growth. Supply of flour with G. lucidum mycelia obtained by solid state fermentation (wheat grain) for rabbits was also evaluated. Mycelium of G. lucidum developed very well in all agricultural residues, soybean hulls was the residue that presented higher growth rate and higher concentration of β-glucans. In the cultivation media experiment, G. lucidum also developed well, media that contained cellobiose and tyrosine, despite presenting lower growth rates and total growth within 10 days, produced mycelia with higher concentration of β-glucans and trolox equivalent antioxidant capacity (TEAC), respectively. Rabbits did not show any sign of intolerance to feed with different concentrations of flour with G. lucidum mycelium. All performance parameters and dressing percentages were adequate to the age at which they were slaughtered. Histological evaluation of organs presented alterations in renal cells (tubular and glomerulus), indicating a possible renal lesion according to the increase of flour with mycelium in feed. Histomorphometric evaluation showed increased vilous height in ileum and decreased vilous width of jejunus at 0.5% concentration, and decrease in crypt diameter according to the increase of concentration of flour with mycelium in feed. These results indicate the possibility of more studies regarding the aspects about cellobiose and tyrosine utilization for the production of bioactive compounds, and about toxicity of this mushroom mycelia, assuring the safety in supplying this product for animails.